FIGURATIVE LANGUAGE ANALYSIS IN TAYLOR SWIFT 'EXILE' SONG LYRIC - Amanda, Azzahrah Putri; Zulri, Alda F.; Amanda, Azzahrah P.; Sari, Dwi L. (Journal of English Language and Literature Teaching, 2023)
Figurative language is a system of sound symbols produced from human speech that gives a text a special aesthetic value. It is found in literary works such as novels, short stories, books, poetry, films, and songs. The poets who use figurative language as part of their literary works as a means of media to say and express a meaning or the meaning of their literary creations. The role of figurative language is to play a role in the construction of a wider message. The study was used an objective theory using qualitative descriptive research method in theory proposed by Knickerbocker. This study wants to learn about the meaning of figurative language, analyze figurative language in song lyrics, and understand the types and meanings of figures of speech in the lyrics of the song ‘Exile’ by Taylor Swift and Bon Iver. The result of figurative language that mainly found as dominant in the lyrics was Irony.